The Optimal Time to Privatize Oil Public Sector in Saudi Arabia - Foudeh, Musa (International Journal of Energy Economics and Policy, 2018)
Based on Jiahua Che dynamic model of privatization (2007) and the experience of privatizing the Mexican petroleum company (Pemex) in 2013, this paper tries to answer this question: Is it time to privatize Aramco? The paper concludes that Aramco will not be privatized, at least during the year 2018, due to the Saudi budget dependence on oil, low level of private property rights, lack of transparency and absence of financial disclosure. Keywords: Saudi Arabia economy, Privatization, Government ownership, Private ownership. JEL Classifications: O53, L33, L20